Institutional rearing is associated with lower general life satisfaction in adulthood - David Richter; Sakari Lemola (Deutsches Institut für Wirtschaftsforschung (DIW), 2013)
We analyzed whether individuals reared in institutions differ in their general life satisfaction from people raised in their families. The data comprised of 19,210 German adults (51.5% female) aged from 17 to 101 years and were provided by the SOEP, an ongoing, nationally representative longitudinal study in Germany. Compared to people raised in families, individuals reared in institutions reported lower general life satisfaction in the manner of a dose response relationship controlling their parents' 8ucation and occupational prestige. The association was moderated by participants' age such that with increasing age the association between institutional rearing and lower general life satisfaction decreased. Further, the relationship was partly mediated by the individuals own education/socioeconomic attainment in adulthood, physical health, and relationship status.
Keywords: 330; life satisfaction; set point theory; early adversity; institutional rearing